1966
DOI: 10.1103/physrev.143.588
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Produced by Energetic Germanium Atoms within a Germanium Lattice

Abstract: The energy dependence of the ionization produced in germanium by energetic germanium atoms was measured. Germanium solid-state detectors served simultaneously as crystalline Ge sample, neutron target, and ionization detector. The spectrum of ionization produced by prompt Ge recoil atoms energized by monoenergetic neutron bombardment was observed in a pulse-height analyzer, and the edge of the spectrum was identified with the ionization produced by Ge recoil atoms having the calculated maximum recoil energy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…The elastic collisions of neutrons with atoms in the detector volume produce nuclear recoils. The energy of the recoils is constrained by the use of monoenergetic neutron beams, the detection of the neutron scattering angle and/or its time-of-flight [5,6,7,8,9,10]. It is then observed that the ionization yield for a nuclear recoil is a factor Q ∼ 0.25 smaller than that produced by an electron recoil of equal energy.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic collisions of neutrons with atoms in the detector volume produce nuclear recoils. The energy of the recoils is constrained by the use of monoenergetic neutron beams, the detection of the neutron scattering angle and/or its time-of-flight [5,6,7,8,9,10]. It is then observed that the ionization yield for a nuclear recoil is a factor Q ∼ 0.25 smaller than that produced by an electron recoil of equal energy.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the theoretical difficulties, the attention is focused on pure substances: hence only symmetric projectile/target atom combinations will be investigated. From all the avail-able measurements, known to the authors, the following are then selected: Si [3,4], Ge [5,6], and liquid Xe [7,8,9,10]. Liquid Ar will also be considered on account of its interest for dark matter searches.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dominant uncertainties come from the uncertainties in the Lindhard theory at very low energy. However, it is usually believed that the Lindhard the- ory describes experimental data well [41,42,43,44], although the experimental uncertainties are quite large at low energy.…”
Section: Comparison Of Model Prediction With Datamentioning
confidence: 99%